1977
DOI: 10.1093/infdis/135.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus-Like Agent in Acute Epidemic Gastroenteritis in Japanese Infants: Fecal Shedding and Serologic Response

Abstract: The reovirus-like agent, sometimes referred to as duovirus or rotavirus, was visualized by electron microscopy in stool extracts from Japanese infants and young children with acute epidemic gastroenteritis. The virus particles measured 70 nm in diameter and had double-shelled capsids. One hundred ten (89%) of 124 patients with the gastroenteritis had such virus particles in stools obtained during the acute phase. The virus particles were excreted in the stools usually during the first eight days of illness. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…Enlarged mesenteric nodes and nodal aggregates are often observed during the surgical correction of intussusception [14,17,19]. Konno et al [22], using autopsy material, reported that hyperplasia of the intestinal lymphoid tissue occurs in acute gastroenteritis caused by rotavirus infection. Pathological data on resected bowel from intussusceptions associated with the now-withdrawn rotavirus vaccine identified lymphoid hyperplasia as possible lead points [23].…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged mesenteric nodes and nodal aggregates are often observed during the surgical correction of intussusception [14,17,19]. Konno et al [22], using autopsy material, reported that hyperplasia of the intestinal lymphoid tissue occurs in acute gastroenteritis caused by rotavirus infection. Pathological data on resected bowel from intussusceptions associated with the now-withdrawn rotavirus vaccine identified lymphoid hyperplasia as possible lead points [23].…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak prompted Konno et al to perform a virological study in 1975 following the method of Bishop et al From this period, some of results about reovirus‐like agent or rotavirus infection have started to be reported in Japan. 19–21 …”
mentioning
confidence: 99%
“…Reports have universally shown that rotavirus particles can be seen in the stools of 15 to 90% of infants with diarrhoea but are absent from the stools of most healthy children. The highest isolation rates have been in temperate climates, particularly in the winter months (Bishop et al, 1974;Davidson et al, 1975;Kapikian et al, 1976;Dupont et al, 1977;Konno et al, 1977;Schoub et al, 1977;Walker-Smith, 1978).…”
mentioning
confidence: 99%